(3GdehGba aj HYV GTGQGJ GdbQGAGJs - (3YHO GdbGOQ Hf eMjj GdOjf Hf eUWaj GdMSfj GdLRGFQj,J (B1300 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg (B: (3Gdehba GdSGOS hGdGQHYhf cd ef YdjgG aGf hGdafGA VO GdhLhO hZdW GdMSf ajeG jOQcg s
(3BNQgG (B:s
(3BNQ GdehLhO efg (B: (3Chef LgI GdhLg GdNGU Hg agh Ydi HUjQI hHjfg ai cd eG jCJi hjRQ hChGeQ GdMb JYGdi s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B45s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs